PEMBELAJARAN EKSTRAKURIKULER PADUAN SUARA DI SMP NEGERI 172 JAKARTA - Sigiro, Junner (Jurnal Penelitian Musik, 2020)
This study aims to describe and develop the choir extracurricular enthusiasm in SMP Negeri 172 Jakarta in a descriptive qualitative manner. The topic of this writing is the learning process, facilities / infrastructure, teacher trainer, and choir member students. The choir training was held with programmed steps with a scheduled implementation time of Tuesday with 60 minutes allocated time starting at 14.00 - 15.00 WIB. The choir extracurricular learning activities in SMP 172 are a kind of choir namely female voice with two voices, soprano and alto, which apply basic vocal techniques including good posture when singing, breathing, solfegio exercises, pronunciation/articulation, correct phrasering exercises. Choir extracurricular learning includes; implementation planning, evaluation (evaluation) and carrying capacity of inadequate training room infrastructure